Analysis of monetary policy responses after financial market crises in a continuous time New Keynesian Model - Bernd Hayo; Britta Niehof (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
We develop a dynamic stochastic full equilibrium New Keynesian model of two open economies based on stochastic differential equations to analyse the interdependence between monetary policy and financial markets in the context of the recent financial crisis. The effect of bubbles on stock and housing markets and their transmission to the domestic real economy and the contagious effects on foreign markets are studied. We simulate adjustment paths for the economies under two monetary policy rules: an open-economy Taylor rule and a modified Taylor rule, which takes into account stabilisation of financial markets as a monetary policy objective. We find that for the price of a strong hike in inflation a severe economic recession can be avoided under the modified rule. Using Bayesian estimation techniques, we calibrate the model to the case of the United States and Canada and find that the resulting economic adjustment paths are similar to those of the theoretical model.
Keywords: C02; C63; E44; E47; E52; F41; 330; New Keynesian Models; Financial Crisis; Dynamic Stochastic Full Equilibrium Continuous Time Model; Taylor Rule